Language Psychology Approach on Language and Literatureâs Learning Process: A Model to Educate the Nation - Sastra, Gusdi (ASPENSI in Bandung, Indonesia, 2014)
ABSTRACT: For getting the young generation that like in reading and usual in writing, absolutely, not as easy as fold back the palm. There are many things should be involved, not only human resources but also various supporting factors, so it can grow up the interest in reading and writing on young generation. The factor of time also has role, because growing up the interest in reading is a process, and each process needs time and patient. This paper discusses on model of Indonesian language and literatureâs learning process based on language psychology (psycholinguistics) to educate the nation, through three steps of mental process, they are: comprehension, production, and bio-neurology. This model is hoped to be applied to teachers and Elementary School studentsâ grade 4th to grade 12th of Senior High School. The arrangement of this model involves the roles of teachers, government, and parents for establishing the education paradigm that can educate the nation. Based on the psychology and language neurologyâs study, therefore, has been arranged a plain model of Indonesian language and literatureâs learning process, that is MENUNDAS (âMembacaâ or Reading + âMenulisâ or Writing Ã âCerdasâ or Intelligent). MENUNDAS is acquired through the famous Indonesian literatureâs book that be internalized through activating of sensory and motoric area, so that the intellectual development of nation mentality is existed.KEY WORD: Psycholinguistics, Indonesian language and literature, mental process, reading, writing, intelligent, and intellectual development of nation.Â RESUME: âPendekatan Psikologi Bahasa pada Proses Pembelajaran Bahasa dan Sastera: Sebuah Model untuk Mendidik Bangsaâ. Untuk mendapatkan generasi muda yang suka membaca dan biasa menulis, sesungguhnya, tidak semudah membalikkan telapak tangan. Ada banyak hal yang harus dilibatkan, tidak hanya sumber daya manusia tetapi juga berbagai faktor pendukung, sehingga dapat tumbuh dan berkembang mengenai minat baca dan menulis di kalangan generasi muda. Faktor waktu juga memiliki peran, karena perkembangan minat membaca adalah suatu proses, dan setiap proses membutuhkan waktu dan kesabaran. Makalah ini membahas model proses pembelajaran bahasa dan sastera Indonesia berdasarkan pada psikologi bahasa (psikolinguistik) untuk mencerdaskan bangsa, melalui tiga tahap proses mental, yaitu: pemahaman, produksi, dan bio-neurologi. Model ini diharapkan dapat diterapkan pada guru dan siswa kelas 4 SD (Sekolah Dasar) sampai dengan kelas 12 SMA (Sekolah Menengah Atas). Penyusunan model ini melibatkan peran guru, pemerintah, dan orang tua untuk membangun paradigma pendidikan yang dapat mencerdaskan bangsa. Berdasarkan kajian psikologi dan neurologi bahasa, kemudian, telah disusun model sederhana dalam proses pembelajaran bahasa dan sastera Indonesia, yaitu MENUNDAS (Membaca + Menulis Ã Cerdas). MENUNDAS diperoleh melalui buku sastera terkenal Indonesia yang diinternalisasikan melalui pengaktifan ranah sensorik dan motorik, sehingga perkembangan intelektual tentang mentalitas bangsa terwujud.KATA KUNCI: Psikolinguistik, bahasa dan sastera Indonesia, proses mental, membaca, menulis, cerdas, dan pengembangan intelektual bangsa.About the Author: Gusdi Sastra, Ph.D. is a Lecturer at the Faculty of Humanities UNAND (Andalas University), Limau Manis Campus, Padang, West Sumatera, Indonesia. For academic interests, the author is able to be contacted via e-mail at: sastra_budaya1990@yahoo.comHow to cite this article? Sastra, Gusdi. (2014). âLanguage Psychology Approach on Language and Literatureâs Learning Process: A Model to Educate the Nationâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.7(2) November, pp.223-230. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (October 9, 2013); Revised (October 28, 2014); and Published (November 20, 2014).